Effects of high-flux hemodialysis and hemodiafiltration on the mortality of patients with end-stage kidney disease: a meta-analysis - Sihui Ma; Nan Pu; Juan Ma (Renal Failure)
Background High-flux hemodialysis (HFHD) is widely used in hemodialysis centers and is the mode of hemodialysis actively recommended by the guidelines. Additionally, hemodiafiltration (HDF) is widely used in clinical practice. However, there are some inconsistencies in the results of studies on the effects of HDF and HFHD, which has caused controversy regarding which of these two dialysis modalities to select.Objective To explore the effect of HFHD and HDF on the survival of patients with end-stage kidney disease (ESKD).Methods A systematic search of the PubMed, EMBASE, Cochrane Library, CNKI, Wanfang, and VIP databases was conducted, focusing on cohort studies and randomized controlled trials on hemodialysis in patients with ESKD using HFHD or HDF. A meta-analysis of all-cause mortality and cardiovascular mortality was conducted using Review Manager 5.3 software, and fixed and random effect models were applied according to the heterogeneity results.Results A total of 13 studies, including six cohort studies and seven randomized controlled trials, were included in the final analysis. The results revealed that HFHD had no statistically significant effect on the all-cause mortality (odds ratio (OR): 1.16, 95% confidence interval (CI): 0.86, 1.57) or cardiovascular mortality (OR: 0.86, 95% CI: 0.64, 1.15) of patients with ESKD. However, compared with HDF, HFHD reduced the infection mortality rate (OR: 0.50, 95% CI: 0.33, 0.77).Conclusions Compared with HDF, HFHD has no obvious benefits for all-cause mortality or cardiovascular mortality in patients with ESKD, but reduced risk of infection-related death.